Seasonal variations in biochemical (biomolecular and amino acid) compositions and protein quality of particulate organic matter in the Southwestern East/Japan Sea - Jo, Naeun; Youn, Seok-Hyun; Joo, HuiTae; Jang, Hyo Keun; Kim, Yejin; Park, Sanghoon; Kim, Jaesoon; Kim, Kwanwoo; Kang, Jae Joong; Lee, Sang Heon (Frontiers in Marine Science, 2022)
The biochemical compositions of marine particulate organic matter (POM) can provide significant information to understanding the physiological conditions of phytoplankton and food quality for their potential consumers. We investigated the seasonal variations in biomolecular and amino acid (AA) compositions of the bulk POM in the southwestern East/Japan Sea from four different sampling months (February, April, August, and October) in 2018. In terms of the biomolecular composition of the POM, overall carbohydrates (CHO) were predominant among three biomolecules accounting for 48.6% followed by lipids (LIP; 35.5%) and proteins (PRT; 15.9%) in the East/Japan Sea. However, markedly seasonal differences in the biomolecular composition of POM were found from February to October, which could be due to seasonally different conditions favorable to phytoplankton growth. Dominant AA constituents to trace POM lability were glycine (GLY), alanine (ALA), and glutamic acid (GLU), suggesting that our POM was the mixtures of decomposing and fresher materials. Furthermore, the significantly negative correlation between the proportion of total essential amino acids (EAAs) and PRT composition (r = -0.627, p< 0.01) was probably reflected by nutrient availability to phytoplankton partitioning EAAs or non-essential AAs (NEAAs). The different biomolecular compounds under un- or favorable growth conditions for phytoplankton could determine the nutritional quality of POM as potential prey as well as degradation status of POM. Therefore, the biochemical compositions of phytoplankton-originated POM hold important ecological implications in various marine ecosystems under ongoing climate changes.